Does China still need to deepen its opening up? – Based on the perspective of reducing CO2 emissions - Yang, Lin; Yuan, Shichao; Lu, Zhengnan (Frontiers in Environmental Science, 2025)
Institutional opening, which signifies a higher level of opening up to the world, enhances the linkage effect of domestic and international resources, breaks down institutional barriers, and achieves optimized allocation of factors. Energy consumption and carbon emission standards of Chinese products will be more integrated with international standards. Thus, reducing the carbon content of export products has emerged as a critical concern. In this context, this paper has used a fixed-effect model to analyze the impact of opening up on China’s overall carbon emission reduction and has explored the transmission path from the opposite direction of export product and technology import. The results are as follows: 1) The level of opening up can effectively reduce China’s total carbon emissions; 2) The quality of export products plays a positive intermediary role in this impact; 3) Technology import reduces overall carbon emissions by improving the quality of exported products. 4) The carbon emission reduction effect of opening up is more obvious in non-coastal areas and the Belt and Road provinces. Based on the empirical results, this paper has put forward several policy suggestions for the government and enterprises.